Plastic soup an atlas of ocean pollution - Roscam Abbing, Michiel (Island Press, 2019)
Plastics have transformed every aspect of our lives. Yet the very properties that make them attractive - they are cheap to make, light, and durable - spell disaster when trash makes its way into the environment. Plastic Soup: An Atlas of Ocean Pollution is a beautifully-illustrated survey of the plastics clogging our seas, their impacts on wildlife and people around the world, and inspirational initiatives designed to tackle the problem. In Plastic Soup, Michiel Roscam Abbing of the Plastic Soup Foundation reveals the scope of the issue: plastic trash now lurks on every corner of the planet. With striking photography and graphics, Plastic Soup brings this challenge to brilliant life for readers. Yet it also sends a message of hope; although the scale of the problem is massive, so is the dedication of activists working to check it. Plastic Soup highlights a diverse array of projects to curb plastic waste and raise awareness, from plastic-free grocery stores to innovative laws and art installations. According to some estimates, if we continue on our current path, the oceans will contain more plastic than fish by the year 2050. Created to inform and inspire readers, Plastic Soup is a critical tool in the fight to reverse this trend.